2011
DOI: 10.1088/0953-4075/45/1/015601
|View full text |Cite
|
Sign up to set email alerts
|

A doubly distorted-wave method for atomic ionization by ultrashort laser pulses

Abstract: We study a time-dependent distorted-wave formulation of atomic ionization by short laser pulses named the double-distorted Coulomb-Volkov (DDCV) approximation. The method takes into account the distortions introduced by the laser field in the initial and final channels, both by means of the Volkov phase. The DDCV model is applied to evaluate electron emission distributions for hydrogen atoms ionized by multi-cycle laser pulses. Results are compared with the predictions of an exact treatment based on the numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…(8) has been widely used to describe the emitted electron immersed in the laser field. For example the Strong Field Approximation (SFA) [12,13,17,22], the Coulomb-Volkov Approximation (CVA) [5,8,11,15,23] and the semiclassical application of the Simple Man's Model (SCM) [3,4,6] employ the non-stationary Volkov state as final wavefunction. The use of length gauge for the perturbation potential, i.e.…”
Section: Above Threshold Ionizationmentioning
confidence: 99%
“…(8) has been widely used to describe the emitted electron immersed in the laser field. For example the Strong Field Approximation (SFA) [12,13,17,22], the Coulomb-Volkov Approximation (CVA) [5,8,11,15,23] and the semiclassical application of the Simple Man's Model (SCM) [3,4,6] employ the non-stationary Volkov state as final wavefunction. The use of length gauge for the perturbation potential, i.e.…”
Section: Above Threshold Ionizationmentioning
confidence: 99%
“…A wealth of information is encoded in this high-energy above-threshold ionization part of the photoelectron spectra about both (i) the driving laser field and (ii) the structure of the target [30,31] (via its scattering cross section [32,33]). Moreover, high-energy above-threshold ionization is more robustly accessible to theoretical modeling than the low-energy part of photoelectron spectra, which is plagued by the necessity to take Coulomb corrections into account [34][35][36][37][38][39].…”
mentioning
confidence: 99%
“…, which simply consists of the product of a Coulomb state and the Volkov phase, cannot account for this effect [11,44]. Effectively it has been shown that the introduction of the quiver motion provides better results [48]. Since it accounts for the KH frame, i.e.…”
Section: A Comparison Of the Various Wave Functionsmentioning
confidence: 99%